A novel model for steam transportation considering drainage loss in pipeline networks. (15th February 2017) - Wang, Hai; Wang, Haiying; Zhu, Tong; Deng, Wanli
Highlights: Drainage loss terms are involved in a proposed steam transportation model. The proposed model achieves accurate estimation of drainage/heat loss along pipes. The proposed model was validated via cases of one single pipe and pipe-network. Saturated steam model was also presented. Abstract: High temperature steam is still used widely in many industries. And waste steam from some industries can still be used as supplement heat sources for district heating and cooling. Drainage recovery is very valuable during steam transportation and distribution in district heating or industry heating projects in order to save energy and water. However, drainage amount collected by steam traps along the pipes can hardly be estimated precisely. A novel model was proposed in this paper to improve the simulation of steam transportation in pipes with consideration of the amount of drainage loss. In the proposed model, drainage involved terms which emblem the continuous mass loss and energy loss during the steam transportation included in mass conservation equation and energy conservation equation respectively. The proposed model was compared with models from other literatures analytically. Furthermore, the simulation results of the proposed model were validated by two steam transportation cases from Baoshan Iron & Steel Co. Shanghai. In case 1, the simulation of steam transportation in a single long pipe showed that the proposed model could achieve more accurate results than previous models. The difference between the simulation results and measured data from on-site experiment was 2.34 K (0.44%) for outlet steam temperature and 0.038 kg/m 3 (0.56%) for outlet steam density. In case 2, the simulation of steam transportation and distribution in a steam network showed that maximum relative differences between results of proposed model and measured data from meters of a steel plant were no more than 5%.